KSU Students’ Attitudes towards Twitter as a Platform for Knowledge Exchange - Alsubaie, Sumayyah Mohammed; Alanazy , Manal Mohammad (Dirasat: Educational Sciences, 2024)
Objectives: The study aims to investigate the attitudes of students from the College of Education at King Saud University towards Twitter. It seeks to identify the type of knowledge shared among users within the College of Education community on Twitter and to explore the perceptions of those students regarding Twitter’s effectiveness in fascillitaing knowledge exchange. Methods: The study employs a mixed-method approach, combining quantitative and qualitative methodologies. Data from students at King Saud University was collected and analyzed using interviews and questionnaires. 23 students participated in the interview, while 451 students completed the questionnaire. Results: The study’s findings indicate that the majority of the participants have positive attitudes towards Twitter as a platform that facilitates diverse knowledge acquisition, particularily within their fields of study. Additionally, topics related to entertainment, art, and religious matters are prominently exchanged among the participants.Moreover, participants acknowledge Twitter’s ability to transcend constriants of time and place, compete with educational institutions, and offer flexible communication. Furthermore, Twitter is perceived to outperform traditional media channels such as television and radio in delivering accurate information. Conclusion: The study recommends enhancing the incorporation of social media, particularily Twitter, into education. As such, it highlights the importance of integrating Twitter into educational settings such as schools and universities. Moreover, the study underscores the necessity of training university students to efffectively use Twitter for knowledge exchange, recognozing it as an apt platform for sharing specialized knowledge.